Խաչատուր Աբովյանին նվիրված ոչ գրքային հրատարակությունները Հայաստանի ազգային գրադարանի արվեստի բաժնում - Գրիգորյան, Սոսե (Հայաստանի ազգային գրադարան / National Library of Armenia, 2023)
The article presents the non-book publications dedicated to Khachatur Abovyan in the art de-partment of the National Library of Armenia. The first original oil painting of the great enlightener was made around 1831. In autumn by the Dorpat artist Ludwig von Meidel. Later, hundreds and thousands of examples were drawn and printed from that blueprint, which are widely used among Armenians. In addition to a large collection of photographs, the art department of the National Library of Armenia preserves exclusive original paintings, postcards, calendars, guides devoted to Abovyan, which are of great value for study.
Գիտամեթոդական էլեկտրոնային հանդես / Գլխավոր խմբագիր` Աննա Չուլյան ; Պատասխանատու խմբագիր՝ Հայկանուշ Ղազարյան ․- Երևան ։ «Գիրք» հրատարակչություն , 2023 ․- N 2 .- էջ 72-76
Keywords: Գրադարանագիտություն, մատենագիտություն և արխիվավարություն